The health benefits of a targeted cash transfer: The UK Winter Fuel Payment - Thomas F. Crossley; Federico Zilio (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Each year the UK records 25,000 or more excess winter deaths, primarily among the elderly. A key policy response is the 'Winter Fuel Payment' (WFP), a labelled but unconditional cash transfer to older households. The WFP has been shown to raise fuel spending among eligible households. We examine the causal effect of the WFP on health outcomes, including self-reports of chest infection, measured hypertension and biomarkers of infection and inflammation. We find a robust and statistically significant six percentage point reduction in the incidence of high levels of serum fibrinogen. Reductions in other disease markers point to health benefits, but the estimated effects are not robustly statistically significant.
Keywords: H51; I12; 330; benefits; health; biomarkers; heating; regression discontinuity